Potential sources of lipid soluble food colorants from selected Malaysian traditional vegetables. - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (2014)
Color is one important characteristics to food products where it dictates consumers' first perception on the foods' flavor and quality. in the current industry, most of the colorants used were coming from synthetic sources. However, due to negative health impacts of the synthetic colorants, we are now witnessing the urgency to find natural colorants and impose it to food products.